Antecedents and Consequences of Technostress among Employees in Digital Work Environments: A Systematic Literature Review - Puspita Sari; Verica Sofie Putibungsu; Retno Dwiyanti; Ugung Dwi Ario Wibowo (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The rapid advancement of digital transformation has increased organizations' reliance on technology to support daily work activities. While digital technologies enhance operational efficiency and productivity, they also expose employees to digital work-related stress, commonly referred to as technostress. This study aims to identify the factors influencing technostress among employees in digital organizations using a Systematic Literature Review (SLR) approach. Relevant articles were retrieved from the Scopus database using the search query TITLE-ABS-KEY (